(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Introduction: The autopsies of those who died due to torture are few in number due to the fact that these individuals’ bodies are frequently covered up, concealing the details of their deaths as well. When it comes to identifying torture, the role of forensic pathologists is becoming more and more crucial. Finding the truth about the medical consequences of fatal torture will raise awareness of torture-related injuries and strengthen forensic humanitarian work. Case report: An unidentified body of a male individual was brought to the mortuary by police for a routine autopsy. As per the information provided by police the apparent cause of death was “Agyaat karan” (Unknown reason). During autopsy, multiple modes of injuries including mechanical, thermal, ligature strangulation, and stress positioning were observed which indicates that the man was tortured to death, and all of these were explained by the dead. Conclusion: As a forensic pathologist, no matter how unreliable history is, if we listen to the tale explained by the dead we can find the truth. The autopsy in the present case proves the cause of death and provides the scientific basis to determine how injuries occurred due to torture.